A Qualified Account of Supererogation: Toward a Better Conceptualization of Corporate Social Responsibility. Issue 2 (4th April 2020) - Tencati, Antonio; Misani, Nicola; Castaldo, Sandro
ABSTRACT: Some firms are initiating pro-stakeholder activities and policies that transcend conventional corporate social responsibility (CSR) conceptions and seem inconsistent with their business interests or economic responsibilities. These initiatives, which are neither legally nor morally obligatory, are responding to calls for a more active role of business in society and for a broader interpretation of CSR. In fact, they benefit stakeholders in a superior and an innovative way and are difficult to reconcile with commonly used rationales in the extant CSR literature, such as win-win opportunities, creating shared value, or corporate philanthropy. For better insight, we develop a qualified account of the concept of supererogation from ethical theory. This account, which examines voluntary responses to moral obligations from which a business is normally excused, is applied to identify the unique features of the initiatives that are not readily understood within conventional reasoning, which is generally focused on a business case.